Circle of days [compact disc, unabridged] - Follett, Ken (Blackstone Publishing, 2025)
Seft, a flint miner, walks the Great Plain in the high summer heat to witness the rituals that signal the start of a new year. He is there to trade his stone at the Midsummer Rite. Joia is a priestess with a vision and an unmatched ability to lead. Her vision of a great stone circle, assembled by the divided tribes of the Plain, will inspire Seft and become their life's work: Stonehenge.